Reviews. Issue 1 (3rd April 2019) - Johnson, Scott; Parang, Elizabeth
Abstract: Elizabeth Parang reviews Reengineering the Library: Issues in Electronic Resources Management . Scott Johnson reviews Academic Library Management: Case Studies.